2016
DOI: 10.1097/md.0000000000004590
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylations of MC4R and HNF4α are associated with increased triglyceride levels in cord blood of preterm infants

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 58 publications
4
24
0
Order By: Relevance
“…Several studies have shown that ( HNF4a ) belongs to the nuclear hormone receptor superfamily (NR2A1) and regulates obesity and metabolic profiles as a transcription factor. DNA methylation of HNF4a can improve triglyceride levels in the cord blood of preterm infants, and can increase the risk of metabolic‐related diseases in adulthood (Kwon et al, , ). Miura et al reported the role of HNF4A in the glucose stimulated insulin secretion by pancreatic β‐cells (Miura et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that ( HNF4a ) belongs to the nuclear hormone receptor superfamily (NR2A1) and regulates obesity and metabolic profiles as a transcription factor. DNA methylation of HNF4a can improve triglyceride levels in the cord blood of preterm infants, and can increase the risk of metabolic‐related diseases in adulthood (Kwon et al, , ). Miura et al reported the role of HNF4A in the glucose stimulated insulin secretion by pancreatic β‐cells (Miura et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation of HNF4a can improve triglyceride levels in the cord blood of preterm infants, and can increase the risk of metabolicrelated diseases in adulthood (Kwon et al, 2016(Kwon et al, , 2018. Miura et al reported the role of HNF4A in the glucose stimulated insulin secretion by pancreatic β-cells (Miura et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Newborn cord blood is an effective biosample for epigenetic epidemiology studies. In published studies based on whole cord blood, DNA methylation associations were identified with prenatal antidepressant exposure [29], fetal growth restriction [30], and cord blood triglyceride levels [31]. Other studies elected to process and extract DNA from buffy coat, and identified associations between DNA methylation and maternal depression or anxiety [32], parental obesity [33], birth weight- for-gestational age [13], and prenatal mercury exposure [34].…”
Section: Discussionmentioning
confidence: 99%
“…Newborn cord blood has often been used in epigenetic epidemiology studies. In whole cord blood, DNA methylation associations were identified with prenatal antidepressant exposure 26 , fetal growth restriction 27 , and cord blood triglyceride levels 28 . Other studies elected to process and extract DNA from buffy coat, and identified associations between DNA methylation and maternal depression or anxiety 29 , parental obesity 30 , birth weight-for-gestational age 13 , and prenatal mercury exposure 31 .…”
Section: Discussionmentioning
confidence: 99%